Vietnamese Universities and Regional Accreditation in the United States - LankfordJonathan W. (TTU Review, 2021)
VIETNAMESE UNIVERSITIES AND REGIONAL ACCREDITATION IN THE UNITED STATES Vietnamese and other Southeast Asian universities view the importanceofnationalaccreditationsecondarytointernationalrecognition. As a result, Southeast Asian regional accreditors are expanding their university networks and forming international standard education in Southeast Asia. However, the link between Asian and American accreditation has yet to be formed, even though America is the number one education destination for internationalstudents. Theresearchpaperthatthisproposalintends to put forth will evaluate the differences in Asian and American regional accreditation; it will highlight potential academic, institutional, and cultural issues that may arise when a Vietnamese university seeks American regional accreditation.